PENGGUNAAN APLIKASI BANTUAN (SAKPA) DALAM MEMPERMUDAH PEMBUATAN LAPORAN KEUANGAN - nurhayati, oky dwi; Ningrum, Alifvia Arvi (Jurnal Sistem Komputer, 2012)
Financial treasure at each agency is required to prepare financial statements which will be reconciled with the KPPN (Office of the State Treasury). The Treasurer shall make an accurate and in accordance with the provisions, it is necessary to review and analysis prior to the report. The reconciliation process must be manually where satker come back and forth to merekon KPPN same data that is not very efficient for satker less far away. So KPPN has done groundbreaking steps to overcome that is through the internet and applications prarekonsiliasi help the SAKPA. SAKPA application is an application used to process data in the User Authorization Budget Accounting System (SAKPA). SAKPA application developed by the Directorate of Treasury Systems as one of the Directorate under the auspices of the Directorate General of Treasury application was developed with the aim Provides ease of the Government Accounting Standard Reporting on Budget User Authorization unit.